Coprological survey of gastrointestinal parasitism in captive wildlife of three zoological parks located in southern India - RAMADEVI, P; VENU, R (The Indian Journal of Animal Sciences, 2020)
Gastrointestinal parasitism (GIP) is one of the important causes of diarrhoea in captive wildlife. Due to lack of systematic data on GIP in captive wildlife of southern parts of India, a study was conducted. Faecal samples (793) were collected from wildlife of three zoological parks, viz. Sri Venkateswara Zoological Park (SVZP), Tirupati (n=244); Indira Gandhi Zoological Park (IGZP), Visakhapatnam (n=221) and Nehru Zoological Park (NZP), Hyderabad (n=328). The collected samples were screened by faecal sedimentation and faecal flotation methods for detection of parasite ova, cysts or oocysts. An overall prevalence of GIP at 19.92% (158/793) with 16.39% (130/ 793) of helminths, 2.27% (18/793) of intestinal protozoa and 1.26% (15/793) of mixed infections were recorded. The highest prevalence of GIP was recorded in NZP (22.26%) followed by SVZP (20.90%) and IGZP (15.38%). The prevalence of GIP was observed highest in reptiles (42.31%) followed by herbivores (26.32%), carnivores (23.59%), birds (9.09%), rodents (9.09%) and primates (8.89%). Monitoring of captive wildlife at regular intervals is needed to assess the GIP to alert the zoo authorities to take up proper preventive measures.